Analisis Kesalahan Penulisan Bahasa Indonesia Pada Skripsi Mahasiswa S1 - Louis Armando Tarigan; Nini Suryani Nini Suryani Nini Suryani; Switri Ramadhani Siregar; Muhammad Surip (Simpati, 2024)
This research evaluates errors in the use of Indonesian in non-Indonesian language and literature students' theses, focusing on aspects of spelling, punctuation, use of italics, and writing particles or affixes. Qualitative descriptive methods are used for in-depth text analysis, identifying language errors in various linguistic fields. The findings show that errors in the use of punctuation marks, especially periods and commas, are dominant with percentages of 53.06% and 38.78% respectively. Spelling errors, especially in the affixes "di-" (42.54%) and "ke-" (31.18%), indicate the writer's confusion in separating or combining the affix with the word that follows it. Grammatical errors, especially in the use of prepositions (40.91%) and conjunctions (31.82%), as well as errors in making effective sentences (27.27%). Phonological errors, such as incorrect use of punctuation, can interfere with a reader's comprehension. This shows that students are often influenced by spoken language in academic writing. In addition, spelling and grammatical errors indicate a lack of understanding of correct Indonesian language rules. To overcome this, it requires increasing understanding of grammar rules, consistent writing practice, and reading good written references. In this way, the quality of students' academic writing can be improved, minimizing errors, and increasing effective scientific communication.